RMS Current of a Photovoltaic Generator in Grid-Connected PV Systems: Definition and Application - P. J. Pérez; G. Almonacid; J. Aguilera; J. de la Casa (International Journal of Photoenergy)
This paper includes a definition of a new and original concept in the photovoltaic field, RMS current of a photovoltaic generator for grid-connected systems. The RMS current is very useful for calculating energy losses in cables used in a PV generator. As well, a current factor has been defined in order to simplify RMS current calculation. This factor provides an immediate (quick and easy) calculation method for the RMS current that does not depend on the case particular conditions (orientation, location, etc.). RMS current and current factor values have been calculated for different locations and modules.